Ability to Write Scientifically with a Local Base Through the Application of the Drill Method of Mathematics - Mariamah, Mariamah; Sulfahri, Sulfahri; Fitriati, Ita; Fitrianingsih, Nur; ., Ilyas; Suciyati, Suciyati; Hardiansyah, Hardiansyah; Salahudin, Salahuddin; Subhan, Subhan; Muhammad, Muhammad; Ramli, Ramli; Ajwar, Muhamad (KnE Social Sciences, 2024)
The problems found in the students’ writings were the use of Indonesian grammar that was not standardized, the use of incorrect punctuation, and the lack of scientific principles in writing proposals. The ideas written have not been systematic and they are not able to develop the ideas in writing activities, so students find it difficult to complete. This research aims to develop students’ writing skills based on local wisdom through the drill method, by conducting an experimental research type of two classes. The instrument used was a writing test and the data were analyzed using the t test at a significant level of 5%. Before conducting the t test, a prerequisite test was carried out, namely the normality test of the data and the homogeneity test. The results showed that the value of t arithmetic is greater than t table so that the accepted hypothesis is an alternative hypothesis, which means that the drill method can develop students’ scientific writing skills. Keywords: ability to write scientifically, application of the drill, mathematics